Preservation of Fe/Mn‐redox fronts in sediments of an oligotrophic, oxygenated deep‐water lake (Lago Fagnano, Tierra del Fuego). Issue 4 (24th February 2022) - Neugebauer, Ina; Thomas, Camille; Ordoñez, Luis; Waldmann, Nicolas D.; Recasens, Cristina; Vizcaino, Alexis; Jimenez‐Espejo, Francisco J.; Ariztegui, Daniel
Abstract: Changing redox conditions in water columns or sediment–water interfaces of lakes are captured as sedimentary archives, and are often influenced by climate. Their study therefore permits the reconstruction of past climate change on (sub‐) annual to longer timescales. In Lago Fagnano (54°S Argentina/Chile), a large oligotrophic and deep‐oxygenated lake, alternations of light grey clay and dark greenish and black laminae are preserved throughout the Holocene sedimentary record. This study aims to clarify the mechanism of laminae formation and preservation in Lago Fagnano, and their relation to changing redox conditions in the lake. High‐resolution major element scanning and mapping along with detailed mineralogical analyses of sediment cores allowed identifying Fe‐oxides, Mn‐oxides and Fe‐(mono) sulphides as responsible for the lamination. Based on the interpretation of redox processes at the current sedimentary redox boundary and of buried palaeo‐redox fronts underlying mass‐transported deposits, the greenish laminae enriched in Fe‐oxides are interpreted as palaeo‐redox fronts. The preservation of such former interfaces in Lago Fagnano sediments is most likely promoted by rapid increases of sedimentation due to higher runoff related to stronger Southern Hemisphere Westerlies. The formation of black laminae, showing only traces of Fe‐(mono) sulphides and organic matter, is obscured by oxidation and early diagenetic processes, i.e. degradation and partial pyritization. These layers were presumably generated by small changes in bottom‐water oxygenation due to reduced mixing and/or higher productivity. This study highlights the value of high‐resolution sediment−geochemical analyses to better understand redox and diagenetic processes in oligotrophic mixed lakes.